Internet of Things based solar panel cooling and monitoring system - Febiola, Anjelika; Dewi, Citra; Mirshad, Emilham; Mulya, Rudi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Solar energy is one of the renewable energy sources that has great potential in Indonesia, due to its abundant availability and zero greenhouse gas emissions. However, the performance of solar panels can degrade due to high temperatures generated by continuous exposure to sunlight. This research aims to design and implement an effective cooling system to increase the output power of solar panels. The system is designed with a real time remote monitoring feature using the Blynk application, and is equipped with an automatic data logging system into Google Sheets. The cooling mechanism is carried out by spraying water onto the surface of the solar panel which is activated based on a predetermined temperature threshold value (set point). The test results show that the system is able to reduce the panel temperature by 5.46°C and increase the output power by 1.76 W. The ratio of power increase to temperature decrease is recorded at 3.1 W/°C, which proves that the system is effective in keeping the panel temperature below 40°C and contributes significantly to the improvement of solar panel performance